2013
DOI: 10.5005/jp-journals-10025-1056
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Corneal Ectasia after Bilateral LASIK: The Thick Flap Counts

Abstract: Purpose: To report a case of post-LASIK corneal ectasia due to a thick flap, while the contralateral eye did not develop ectasia after an incomplete deep flap cut, followed by a thinner flap LASIK procedure.Methods: Case report. Conclusion:Unilateral ectasia after LASIK may occur due to a thick flap which leads to biomechanical failure of the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Corneal ectasia has been a severe complication of LASIK surgery since the first report by Seiler in 1998 [ 27 ]. Clinical risk factors associated with ectasia include preoperative ectactic corneal disease, young age, and low preoperative pachymetry [ 21 , 28 , 29 , 30 ].…”
Section: Screening For Ectasia Risk Before Laser Vision Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal ectasia has been a severe complication of LASIK surgery since the first report by Seiler in 1998 [ 27 ]. Clinical risk factors associated with ectasia include preoperative ectactic corneal disease, young age, and low preoperative pachymetry [ 21 , 28 , 29 , 30 ].…”
Section: Screening For Ectasia Risk Before Laser Vision Correctionmentioning
confidence: 99%
“…Some of these studies found a comparatively lower sensitivity for the VAE-NT eyes (some with typical topography and tomography—NTT). However, it is pertinent to note that various of these cases could be genuinely unilateral ectasia due to mechanical trauma [ 30 , 59 ]. Recently, a novel optimized version of the TBI (TBIv2) was developed with significantly higher accuracy (0.945) for detecting VAE-NT (84.4% sensitivity and 90.1% specificity; cutoff 0.43) and similar AUC for clinical ectasia (0.999; 98.7% sensitivity; 99.2% specificity; cutoff 0.8).…”
Section: Corneal Biomechanical Assessmentmentioning
confidence: 99%
“…[ 3 30 31 33 33 34 ] Although some of these studies have found a moderately lower sensitivity for the VAE-NT eyes (some with normal topography and tomography – NTT), it is important to a reminder that some cases may be truly unilateral ectasia due to mechanical trauma. [ 35 36 ]…”
Section: Ntegration Of C Orneal S ...mentioning
confidence: 99%